Integrating Education and Entrepreneurship: Strategic Business Development at Pesantren in the Era of Digital Disruption - Siti Nurhasanah Yahya; Mulyawan Safwandy Nugraha; Elvira Sitna Hajar; Neila Aisha; Satria Adi Pradana (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
This study aims to conduct an in-depth analysis of business development strategies carried out in various business units in the Pesantren Nurul Iman Parung Bogor in the era of digital disruption. This study uses qualitative descriptive research methods, with data collection methods through observation, interviews, and document collection related to the focus of the research. Data analysis includes data reduction, display, and conclusion drawing/verification. The business development strategy of Pesantren Nurul Iman Parung Bogor follows four key steps aligned with their entrepreneurial practices. First, focus on business idea development by recycling waste to create new opportunities and generate revenue. Second, expand business scale by increasing machine capacity, workforce, and investment capital, as shown by the establishment of 26 business units. Third, expand business scope by opening new locations and developing different types of businesses, such as the Active Carbon and Nurul Iman Animation ventures. Lastly, they pursue expansion through partnerships, collaborating with PT. Asj Indonesia and the Ministry of Industry to create new business units. These strategies form the foundation of their business growth, emphasizing capacity building and diversification to ensure economic sustainability. This research highlights the potential of pesantren-based business models in encouraging economic sustainability by integrating entrepreneurial practices into pesantren operations. This research is also a reference to promote the development of policies supporting entrepreneurship education integration in faith-based educational institutions. This Pesantren is a concrete example of how collaboration between academic institutions, the industrial sector, and the government can create an educational ecosystem oriented toward economic sustainability.